2014
DOI: 10.1161/circulationaha.114.011848
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Inhalation During Normoxic Resuscitation Improves Neurological Outcome in a Rat Model of Cardiac Arrest Independently of Targeted Temperature Management

Abstract: Background-We have previously shown that hydrogen (H 2 ) inhalation, begun at the start of hyperoxic cardiopulmonary resuscitation, significantly improves brain and cardiac function in a rat model of cardiac arrest. Here, we examine the effectiveness of this therapeutic approach when H 2 inhalation is begun on the return of spontaneous circulation (ROSC) under normoxic conditions, either alone or in combination with targeted temperature management (TTM). Methods and Results-Rats were subjected to 6 minutes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
94
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(99 citation statements)
references
References 49 publications
5
94
0
Order By: Relevance
“…Transient global cerebral ischemia could lead to delayed neuronal loss and activation of microglia and astrocytes in selectively vulnerable areas, such as the hippocampal CA1 22. As indicated in the histological analysis of the hippocampal CA1 region in Figure 4, TTM or GBC alone significantly recovered numbers of neurons by NeuN staining compared to NT treatment, with their combination resulted in a further recovery (Figure 4A and 4E).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Transient global cerebral ischemia could lead to delayed neuronal loss and activation of microglia and astrocytes in selectively vulnerable areas, such as the hippocampal CA1 22. As indicated in the histological analysis of the hippocampal CA1 region in Figure 4, TTM or GBC alone significantly recovered numbers of neurons by NeuN staining compared to NT treatment, with their combination resulted in a further recovery (Figure 4A and 4E).…”
Section: Resultsmentioning
confidence: 88%
“…In humans, TTM is suggested to be maintained for at least 24 hours after achieving target temperature 2. However, shorter duration of TTM was commonly utilized in animal studies, because of the high metabolic rate of rodents and shorter time in reaching target temperature 22, 29, 30. Ye et al 31.…”
Section: Discussionmentioning
confidence: 99%
“…In 2007, Ohsawa et al [24], found that hydrogen act as a therapeutic antioxidant by selectively reducing cytotoxic oxygen radicals, especially hydroxyl radical (OH·), the most cytotoxic reactive oxygen species (ROS). In recent years, hydrogen gas (H 2 ) or hydrogen-rich saline are widely accepted to exert protective effects in many diseases including myocardial ischemia-reperfusion injury, neuropathic Pain, brain injury via regulating oxidative stress, inflammatory response and apoptosis [25-28]. Except in rat model, the protective effects of inhaling H 2 in myocardial ischemia-reperfusion injury also have been reported in dog model and patients experiencing ST-elevated myocardial infarction [29, 30].…”
Section: Introductionmentioning
confidence: 99%
“…Recent proof-of-concept studies in animal models have demonstrated the therapeutic effect of molecular hydrogen (H2) on neurological outcomes after cardiac arrest (CA). 3, 4 In this study, we sought to evaluate the feasibility and safety of H2 inhalation (HI) for PCAS.…”
mentioning
confidence: 99%